STRUKTUR TATA KELOLA PERUSAHAAN DAN LUAS PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi empiris pada perusahaan industri dasar dan kimia yang terdaftar di Bursa Efek Indonesia) - Yoseph Dimas Edo Perwira; Paulus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2013)
This study examines the effects of corporate governance structures to the size of corporate social responsibility disclosure in a firm’s annual reports. This size of corporate social responsibility disclosure includes environment, energy, employee’s health and safety, employee’s other needs, products, community involvement, and others. Previous research review show that there is no consistency and give many variety results. This study attempts to examine it with 7 independent variables (4 research variables and 3 control variables). These variables are independent commissioner, audit committee, public ownership, foreign ownership, profitability, leverage, and firm’s size.Sample that used in this study was extracted with using purposive sampling method. The population is 57 basic and chemical industry firms that listed in Indonesian Stock Exchange (IDX). Research periods are 2010 and 2011. After reduces with several criteria, 37 firms are determined as firms samples and 68 annual reports as research samples. The analysis technique in this study uses a multiple regression analysis with help from a program named SPSS. The result indicates that no research variables show any significant effects because the structures of corporate governance in Indonesia aren’t implemented effectively. Leverage and firm’s size as control variables have significant effects to the size of Corporate Social Responsibility (CSR) disclosure in a firm’s annual reports.